2019
DOI: 10.3389/fpls.2019.00214
|View full text |Cite
|
Sign up to set email alerts
|

Root-Associated Fungal Communities From Two Phenologically Contrasting Silver Fir (Abies alba Mill.) Groups of Trees

Abstract: Root-associated fungal communities are important components in ecosystem processes, impacting plant growth and vigor by influencing the quality, direction, and flow of nutrients and water between plants and fungi. Linkages of plant phenological characteristics with belowground root-associated fungal communities have rarely been investigated, and thus our aim was to search for an interplay between contrasting phenology of host ectomycorrhizal trees from the same location and root-associated fungal communities (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 76 publications
5
12
0
Order By: Relevance
“…Previously, Perez-Izquierdo and colleagues [19] found that the genotypes of Pinus pinaster is clearly structuring the associated fungal communities. Similar impacts on fungal communities were found for different genotypes of the broadleaf Populus [18] and varying phenotypes of Abies alba [17]. In contrast to the mentioned studies [17][18][19], which used trees of higher ages and bigger diameter at breast height, the beeches in our study were very young, just five years at the second sampling in 2017.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previously, Perez-Izquierdo and colleagues [19] found that the genotypes of Pinus pinaster is clearly structuring the associated fungal communities. Similar impacts on fungal communities were found for different genotypes of the broadleaf Populus [18] and varying phenotypes of Abies alba [17]. In contrast to the mentioned studies [17][18][19], which used trees of higher ages and bigger diameter at breast height, the beeches in our study were very young, just five years at the second sampling in 2017.…”
Section: Discussionsupporting
confidence: 78%
“…Similar impacts on fungal communities were found for different genotypes of the broadleaf Populus [18] and varying phenotypes of Abies alba [17]. In contrast to the mentioned studies [17][18][19], which used trees of higher ages and bigger diameter at breast height, the beeches in our study were very young, just five years at the second sampling in 2017. A comparable approach carried out in a pot experiment led to the same absent progeny effect on EMF communities [35].…”
Section: Discussionsupporting
confidence: 78%
“…et Broome, Paxillus Fr., Tomentellopsis Hjortstam and Xerocomus Quél were not detected in the study. The above-mentioned species were found in fir nursery soil by Schirkonyer et al (2013), Ważny (2014) and Unuk et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many fungal species show phenotypic plasticity and depending on the prevailing conditions, adopt different life strategies -from saprotrophs to endophytes. Their role in the community is not always clear (Vasiliauskas et al 2007, Kowalski 2008, Kuo et al 2014, Jaber et al 2014, Unuk et al 2019. For example, the classification of the Mycena genus is very ambiguous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation